Challenges in drug discovery and description targeting Leishmania spp.: enzymes, structural proteins, and transporters - Mendoza-León, Alexis; Serrano G., María Luisa; Ponte-Sucre, Alicia (Frontiers in Tropical Diseases, 2023)
Leishmaniasis is a complex tropical disease caused by the protozoan parasite Leishmania spp. Classical chemotherapy includes pentavalent antimonial; however, pentamidine, amphotericin B, and miltefosine have been used. Chemo-resistance remains a risk for successful treatment; thus, target identification and development of selective drugs remain a priority in controlling this disease. Evidence indicates that 6-phosphogluconate dehydrogenase (6PGDH), β-tubulin protein, and ATP-dependent transporters (ABCs-T) are potential targets to be addressed. The pentose phosphate pathway key enzyme 6PGDH is essential for protecting kinetoplastid parasites from oxidative stress and differs from the mammalian host enzyme (<35% AA sequence identity). An optimized 3D model has been used to select high -affinity compounds toward the enzyme through virtual screening and subsequent evaluation in vivo. In kinetoplasts, tubulins are highly conserved proteins essential for microtubule formation. However, compared to other eukaryotic cells, there is a differential susceptibility of kinetoplastid proteins to antimicrotubular agents, e.g., colchicine resistance. A comparison of experimental models between bovine and Leishmania β-tubulin protein allowed us to identify structural modification products of various amino acid substitutions, which hinder the access of colchicine to the binding pocket of the Leishmania protein. Similar changes are found in the β-tubulin sequence of other kinetoplastids such as Trypanosoma cruzi, T. brucei, and T. evansi. The evaluation of the β-tubulin protein as a therapeutic target and the compounds that selectively interact with it was carried out using in silico approaches. The activities of ABC-Transporters are related to the main causes of drug resistance, and the collected evidence suggests that for the ABC-Transporter blocker glibenclamide, there is a: (1) differential susceptibility of Leishmania spp. vs. macrophages; (2) greater susceptibility of axenic amastigotes vs. promastigotes; and (3) glibenclamide-glucantime synergistic drug interaction in macrophage-infected cells. Herein, we discuss the potential value of designing ABC-Transporter blockers for combination therapy in the treatment of leishmaniasis. The examples mentioned above highlight the importance of the search for new therapeutic targets and pharmacophores for the design of alternative treatments for the disease.